Molecular Docking of Lunacridine from Lunasia amara to DNA : Its Inhibition And Interaction Study Correlated With The Cytotoxic Activity on P388 Murine Leukemia Cells - M. Sulaiman Zubair; Subehan Subehan (Indonesian Journal of Cancer Chemoprevention, 2010)
DNA Topoisomerase II inhibitors are a type of anticancer drugs. These drugs perform their biological activity either by forming a DNA-intercalator-topoisomerase II ternary complex or by inhibiting other enzymes and/or transcription factors that act on DNA. The strong interactions with DNA play a crucial role for their pharmacological properties. Lunacridine, the active principle from Lunasia amara, was known as DNA intercalating Topoisomerase II inhibitor. With the aims to explore the affinity and molecular interaction of lunacridine compound isolated from Lunasia amara with DNA, molecular docking study has been carried out with DNA model using Autodock 4.0 software. Cytotoxicity test on P388 murine leukemia cells was done also using 100, 30, 10, 3 and 1 μg/ml series of lunacridine concentration. The docking result shows that Lunacridine itself could to dock intercalatively between base pairs of DNA and the possibility interaction with adenine, thymine and cytosine by dipole-dipole interaction.  The lowest predicted binding  energy of lunacridine is –6,22 kcal/mol, whereas original ligand bis thiazole is -16,37 kcal/mol. Lunacridine compound itself has less cytotoxic activity on P388 murine leukemia cells with the IC50 value of 39,52 μg/ml or 129,41 μM. The binding energy of lunacridine on DNA higher than original ligand show that the interaction of lunacridine with DNA is not stable afford the less cytotoxic activity. However, based on the IC50 value, lunacridine could be depeloved as anticancer.Key words: docking, lunacridine,  Lunasia amara, cytotoxic, P388 murine leukimia cells.